Trust system architecture for securing GOOSE communication in IEC 61850 substation network - Rashid M.T.A.; Yussof S.; Yusoff Y. (Science and Engineering Research Support Society, 2023)
Electric power system protection; Electric substations; Internet protocols; Network protocols; Standards; Transmission control protocol; GOOSE; IEC 61850; Security attacks; Substation automation; Trust systems; Network security